Operating Carbon-Neutral Tourism: Systematic Review & Bibliometric Analysis - J. P. R. C. Ranasinghe; R. A. D. D. N. Ranatunga; P. G. S. S. Pattiyagedara (Goodwood Publishing, 2022)
Purpose: The primary goal is to identify the existing knowledge on carbon-neutral tourism gained from 2005 to 2023. Research Methodology: To accomplish the research purpose, a systematic literature review (SLR) approach and preferred reporting items for systematic reviews and Meta-analysis (PRISMA) guidelines were used to address the research objective. Through methodical literature research, bibliometric analysis, and the use of the VOS viewer software, all chosen papers were thoroughly reviewed, summarized, and synthesized. Results: Combining The Google Scholar, Emerald Insight, and Lens.ORG databases resulted in 43 articles. An increasing variety of tourism destinations are planning to become